Pengaruh Ukuran Perusahaan Dan Transaksi Afiliasi Terhadap Profitabilitas Serta Penghindaran Pajak Di Subsektor Perdagangan (Universitas Gresik, 2023)
This study aims to determine the Effect of Company Size (Size) and Affiliated Transactions (RTA) on Profitability (ROA) and their impact on Tax Avoidance (ETR) in Large Trading Goods Production Subsector Companies in 2021. This study uses secondary data sourced from financial reports. companies included in the LQ45 list for the period ending in 2021. The number of samples in this study were 21 companies, which made transactions with related parties (Affiliates) based on a purposive sampling technique. The analytical method used is Path. Analysis or path analysis using IBM SPSS Statistics 26 and Microsoft Excel software. Based on the results of this study, Size, RTA and ROA have an effect on tax evasion (ETR) and RTA has no direct effect on ETR